2012
DOI: 10.1161/circep.111.962720
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Anatomy Revisited

Abstract: R ecent decades have seen rapid developments in arrhythmia treatment, especially the use of catheter ablation. Although the substrates of atrial fibrillation, its initiation and maintenance, remain to be fully elucidated, catheter ablation in the left atrium has become a therapeutic option for patients with this arrhythmia. With ablation techniques, various isolation lines and focal targets are deployed; the majority of these are anatomic approaches. It has been over a decade since we published our first artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
257
1
15

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 305 publications
(285 citation statements)
references
References 61 publications
12
257
1
15
Order By: Relevance
“…The LA subendocardium contained 61.9% fibrotic tissue concentrated in the PLA, LA roof, and floor, while the RA subendocardium contained only 25.7% fibrotic tissue, mainly in the LRA (Figure 3A). Our CE‐MRI and other studies30 indicate a thin endocardial layer (0.1–0.7 mm) of predominantly fibrous tissue in the left atria, which explains why the highest percent of fibrosis was observed in the LA endocardium. The functional effect of this endocardial layer of fibrous tissue needs to be evaluated in future studies.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…The LA subendocardium contained 61.9% fibrotic tissue concentrated in the PLA, LA roof, and floor, while the RA subendocardium contained only 25.7% fibrotic tissue, mainly in the LRA (Figure 3A). Our CE‐MRI and other studies30 indicate a thin endocardial layer (0.1–0.7 mm) of predominantly fibrous tissue in the left atria, which explains why the highest percent of fibrosis was observed in the LA endocardium. The functional effect of this endocardial layer of fibrous tissue needs to be evaluated in future studies.…”
Section: Resultssupporting
confidence: 70%
“…The fixation process of the atria may affect size and thickness variation measurements derived from ex vivo CE‐MRI by ≈5% as shown by other studies 49. The computed atrial wall thickness in the left atrial appendage was found to be affected by the extremely complex and trabecular atrial anatomy,30 and thus wall thickness of the left atrial appendage was not reported. The atrial cellular activation model is based on a simplified Fenton‐Karma model, not biophysics‐based cellular models10, 12 for the sake of computational efficiency, although it was validated by optical mapping data in this study and widely used by us15, 27 and others 28.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The LA is situated more posteriorly and superiorly than the right atrium separated by the obliquity of the plane of the IAS. 21 The LA appendage (LAA) is smaller than the right atrium appendage (RAA). Narrower and with different shapes has a distinct opening to the atrial body and overlies the left circumflex coronary artery.…”
Section: Anatomical Considerations and Atrial Muscular Architecture Nmentioning
confidence: 99%
“…The left atrial appendage has many anatomical variants, but it often rests on the lateral aspect of the LV and its tip can span all the way to reach the epicardial LV summit and even touch the RVOT, where the two ventricles meet 4.…”
Section: Case Reportmentioning
confidence: 99%